THE USE OF COMPLEMENTARY THERAPIES IN CHILDREN AND ADOLESCENTS WITH CANCER : A LITERATURE REVIEW - Setyawati, Anita; Mirwanti, Ristina; Nuraeni, Aan (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah., 2021)
Children and adolescents with cancer can experience unpleasant experiences, such as pain, anxiety, fatigue, sleep disturbances, balance disorders, and even mental, behavioral, and emotional disturbances. These negative experiences lead to decrease in quality of life. A recent research indicates that complement therapies can reduce the terrible effects of cancer. So this literature study aimed to identify the use of complementary therapies in children and adolescents with cancer. This study was a literature review that begins with a search for articles on digital databases, Science Direct and Google Scholar, using the keyword